Pengembangan Aplikasi Posyandu Berbasis Web dalam Mendukung Monitoring Gizi Balita untuk Pencegahan Stunting (Studi Kasus : Posyandu Pamuji Rahayu) - Weni Indri Yanti; Ramayanti, Desi (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
This study aims to develop a web-based Posyandu information system to improve the efficiency and accuracy of child health record keeping in preventing stunting. The system was designed to address the challenges faced by Posyandu Pamuji Rahayu in Banyurata Village, Kebumen, which still relies on a manual record-keeping system prone to damage and data loss. Using the Waterfall system development methodology, this study resulted in a system that allows both cadres and parents to access child health data digitally, improving transparency and the effectiveness of monitoring children's growth. The testing results show that the system successfully enhanced efficiency, facilitated data entry, and enabled early detection of stunting through visualizations of children's growth graphs. Despite challenges in digital literacy among cadres and limited internet access in remote areas, the findings indicate that the web-based system has great potential for broader implementation in supporting stunting prevention programs at Posyandu.